Hubungan Pola Makan dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas - Dina Mariana; Dwi Wulandari; Padila Padila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the relationship between eating patterns and the incidence of anemia in pregnant women at the Jalan Gedang Health Center in Bengkulu City. The research method used is descriptive analytic cross sectional design. The results of 30 respondents are half of respondents (50.0%) have unhealthy eating patterns, almost half of respondents (26.7%) have anemia. Based on the Chi-Square test p-value = 0.035. The conclusion from this study shows that there is a relationship between diet and anemia in pregnant women at the Puskesmas Jalan Gedang, Bengkulu City. Keywords: Anemia, Diet, Pregnant Women